2009
DOI: 10.9744/ing.v10i2.16884
|View full text |Cite
|
Sign up to set email alerts
|

Priorities in English Pronunciation Teaching in EFL Classrooms

Abstract: This paper reports the priorities in English pronunciation teaching in Indonesian EFL classrooms focusing on the English varieties, components of pronunciation, and techniques for pronunciation teaching. The results indicated that (1) international English was valued as a more appropriate variety for Indonesian learners, (2) and that while depending on a limited range of rather traditional techniques of pronunciation instruction, Indonesian EFL teachers valued segmental features more than suprasegmental featur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 1 publication
0
2
0
Order By: Relevance
“…This possibility is assumed that Bahasa Indonesia is "not an identity marker in the same way that a first language might be assumed to be" (Lamb & Coleman, 2008;Suharsih, 2017). Furthermore, Moedjito also found that Indonesian English was the least preference by English teachers to become an appropriate model in teaching English for lower secondary schools in West Nusa Tenggara province because of Bahasa Indonesia, which is characterized Indonesian English, was their L2 (Moedjito, 2008).…”
Section: Localized English As Language Instructionmentioning
confidence: 99%
“…This possibility is assumed that Bahasa Indonesia is "not an identity marker in the same way that a first language might be assumed to be" (Lamb & Coleman, 2008;Suharsih, 2017). Furthermore, Moedjito also found that Indonesian English was the least preference by English teachers to become an appropriate model in teaching English for lower secondary schools in West Nusa Tenggara province because of Bahasa Indonesia, which is characterized Indonesian English, was their L2 (Moedjito, 2008).…”
Section: Localized English As Language Instructionmentioning
confidence: 99%
“…According to Wei and Zhou (2002), English pronunciation was neglected in some universities in Thailand. In Indonesia, although secondary school students really need to learn pronunciation, most teachers do not know what to teach and how to teach it (Moedjito, 2008).…”
Section: Negligence Of Pronunciation Instruction In Eflmentioning
confidence: 99%